PENGARUH AKUPUNKTUR JIN’S 3 NEEDLE TERHADAP PENURUNAN INTENSITAS NYERI DIABETIC NEUROPATHY PERIFER - Kurniawan, Leny Candra; Abdullah, Ikhwan (Faculty of Medicine and Health Science, Universitas Islam Negeri Maulana Malik Ibrahim, 2020)
Diabetic Peripheral Neuropathy is a type of nerve damagethat occurs due to diabetes. High blood sugar levels in thelong term can cause damage to nerve fibers throughout thebody, such as legs, feet, blood circulation, heart, digestivesystem, and urinary tract. Diabetic Peripheral Neuropathy isa serious complication of diabetes that often causes pain inthe limbs. Pain management Diabetic Peripheral Neuropathyis usually by administering pain medication for a long periodof time. These medicines will have side effects. The use ofacupuncture as an alternative to help reduce the intensity ofpain in peripheral diabetic neuropathy has proven to beeffective and relatively without side effects. The advantage ofacupuncture therapy is that it has relatively no side effects.The general aim of this study is to reduce the intensity of painin peripheral neuropathy. The research design usesquantitative methods. The study population was all patientswith peripheral neuropathy who visited the Harmoni HealthyClinic in March-May 2019. The sampling method used wasaccidental sampling. The benefits of this study provide analternative for DM sufferers to reduce the intensity ofneuropathic pain naturally with acupuncture without fear.side effects. From the results of this study it is known thatthere is an influence of Jin’s Three Needle acupuncture inreducing the intensity of pain in Peripheral Neuropathy.Calculations using statistical SPSS 21 with paired sample ttest obtained significant results (0.00) from the value of α(0.05), then H1 is accepted. So with a significance level of5%, it can be concluded that Jin's Three Needle acupuncturecan reduce the intensity of pain in diabetic peripheralneuropathy